Expression and functionality of Toll-like receptor 3 in the megakaryocytic lineage - D'Atri, Lina Paola (2015)
Background: In addition to their key role in hemostasis, platelets and megakaryocytes regulate immune and inflammatory responses, in part through their expression of Toll-like receptors (TLRs). Among the TLRs, TLR3 recognizes dsRNA associated with viral infection. Thrombocytopenia is a frequent complication of viral infection. However, the expression and functionality of TLR3 in megakaryocytes and platelets is not yet well understood. Objective: To study the expression and functionality of TLR3 in the megakaryocytic lineage. Methods and results: RT-PCR, flow cytometric and immunofluorescence assays showed that TLR3 is expressed in CD34+ cells, megakaryocytes, and platelets. Immunoblotting assays showed that stimulation of megakaryocytes with two synthetic agonists of TLR3, Poly(I:C) and Poly(A:U), activated the nuclear factor-κB (NF-κB), phosphoinositide 3-kinase (PI3K)/Akt, extracellular signal-related kinase (ERK)1/2 and p38 pathways. TLR3-megakaryocyte activation resulted in reduced platelet production in vitro and interferon-β release through the PI3K-Akt and NF-κB signaling pathways. TLR3 ligands potentiated the aggregation mediated by classic platelet agonists. This effect was also observed for ATP release, but not for P-selectin or CD40L membrane exposure, indicating that TLR3 activation was not involved in α-granule release. In addition, TLR3 agonists induced activation of the NF-κB, PI3K-Akt and ERK1/2 pathways in platelets. Reductions in platelet production and platelet fibrinogen binding mediated by Poly(I:C) or Poly(A:U) were prevented by the presence of an inhibitor of the TLR3-dsRNA complex. Conclusions: Our findings indicate that functional TLR3 is expressed in CD34+ cells, megakaryocytes, and platelets, and suggest a potential role for this receptor in the megakaryopoiesis/thrombopoiesis alterations that occur in viral infections.